(untitled) (Journal of the Management Sciences, 2025)
The board of directors of a company is expected to develop tax planning strategies to lower the taxable amount owed to the tax authority in order to improve shareholders’ wealth and avoid fraud, but not to engage in tax evasion. This study examined the impact of board attributes on tax planning of listed consumer goods companies in the Nigerian stock exchange (NSE). Ex-post facto research design was used and the population of the study comprised all consumer goods companies which were consistently listed at Nigerian Stock Exchange for the period 2011-2021. Data for the study were obtained from the annual reports and accounts of all listed consumer goods companies for the period under review. Multiple regression analysis technique was used in analyzing the data. The findings revealed that both board gender diversity and board independence has positive and significant impact on Effective Tax Rate of listed consumer goods companies in Nigeria.